Política e politheia nos provérbios romenos do século XVIII - Laura Badescu (Medievalista)
The paper proposes an analysis of the concept “politheia” in relation with Romanian paremiologic corpus used in the eighteenth century. In this framework, it was described three contexts (genetic, generic and functional) that caused mutations in the semantic of paremiologic structures. The intention is to explain these changes by highlighting the connections between sentential statementsand the political, social and cultural zeitgeist.